Rancang Bangun Aplikasi Silase Pakan Ternak Domba Berbasis Android - Irfan Maulana, Dani; Susandi, Dony (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Nowadays, technological developments can be used in all aspects from simple to complex jobs. One of them is in the field of animal husbandry. Silage technology is a fermentation technology commonly used to preserve forage forage. This silage technology is not widely known, most of the people still rely on fresh forage in the form of field grass and the method of calculating silage making still uses manual calculations. As a result, people's farms can never develop, because the provision of feed depends entirely on nature. In an effort to introduce this silage technology to farmers, an Android-based silage application was created. This application is expected to improve people's farming, as well as make it easier for farmers to learn silage technology. Making the application to be built uses RUP as a method in developing the system. and android studio software for making the application.